2004
DOI: 10.1128/jb.186.14.4457-4465.2004
|View full text |Cite
|
Sign up to set email alerts
|

Two Genetic Loci Produce Distinct Carbohydrate-Rich Structural Components of thePseudomonas aeruginosaBiofilm Matrix

Abstract: Pseudomonas aeruginosa forms biofilms, which are cellular aggregates encased in an extracellular matrix. Molecular genetics studies of three common autoaggregative phenotypes, namely wrinkled colonies, pellicles, and solid-surface-associated biofilms, led to the identification of two loci, pel and psl, that are involved in the production of carbohydrate-rich components of the biofilm matrix. The pel gene cluster is involved in the production of a glucose-rich matrix material in P. aeruginosa strain PA14 (L. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
467
0
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 466 publications
(493 citation statements)
references
References 39 publications
21
467
0
5
Order By: Relevance
“…Similar results were obtained using a mutant derivative of the nonmucoid strain P. aeruginosa PAO1 engineered to overproduce alginate (25,60). On the other hand, results using wild-type P. aeruginosa PAO1 and PA14 showed that alginate was not associated with biofilms (72) and that a second polysaccharide likely encoded by a separate polysaccharide biosynthetic gene cluster may provide the extracellular matrix material for those cells (18,19,29). In another report, using P. aeruginosa PAO1, DNA was suggested to be the extracellular matrix material, since the addition of DNase to biofilms dispersed the bacteria (64).…”
supporting
confidence: 69%
“…Similar results were obtained using a mutant derivative of the nonmucoid strain P. aeruginosa PAO1 engineered to overproduce alginate (25,60). On the other hand, results using wild-type P. aeruginosa PAO1 and PA14 showed that alginate was not associated with biofilms (72) and that a second polysaccharide likely encoded by a separate polysaccharide biosynthetic gene cluster may provide the extracellular matrix material for those cells (18,19,29). In another report, using P. aeruginosa PAO1, DNA was suggested to be the extracellular matrix material, since the addition of DNase to biofilms dispersed the bacteria (64).…”
supporting
confidence: 69%
“…Psl was shown contributing to biofilm production, tolerance to oxidizing agents and host defensive processes (Friedman and Kolter, 2004;Jackson et al, 2004;Mishra et al, 2012), that is, traits likely useful in insect interactions.…”
Section: Strain Selectionmentioning
confidence: 99%
“…A recent study describing the EPS of PAO1 biofilms identified the major carbohydrate moieties in this to include glucose, rhamnose, mannose, xylose, 3-deoxy-D-manno-oct-2-ulosonic acid (KDO),N-acetylgalactosamine, N-acetylfucosamine, and N-acetylglucosamine (70). More recently, two genetic loci (psl and pel) responsible for the production of mannose-rich (psl) and glucose-rich (pel) polymer components of P. aeruginosa EPS (18,19,52) were identified. With the exception of KDO with its ionizable carboxylate, most of the sugars described in these studies are neutrally charged or sugars with a possible ionizable amine group (depending on polymeric linkage), which may be difficult to stain.…”
mentioning
confidence: 99%